Is Evidence Able to Persuade Physicians to Discuss Spirituality with Patients? - Saguil, Aaron (Journal of religion and health, 2011)
Patients believe that spirituality informs health; frequently, they wish to share their beliefs with physicians. Although a large number of physicians believe it their responsibility to be aware of patient beliefs, many do not address spirituality because they do not believe it their role to do so. These physicians would perhaps feel differently if presented with evidence that associated spirituality with positive health outcomes. This national sample of family medicine residents were asked if, presented with evidence that spirituality was associated with improved outcomes, they would be more likely to initiate discussions of spirituality with patients. To varying degrees, most residents agreed that they would be more willing to initiate spirituality discussions if presented with good evidence. Geographic region of training, religious preference, and Spiritual Well-Being Scale quartile predicted both strength of agreement and whether a resident would be as responsive to spirituality oriented research as to investigations of traditional therapeutic modalities. Although residents indicated that they would be more responsive to publications on traditional medical therapies, familiarity with the spirituality literature as part of a residency educational curriculum may help break down barriers to addressing this issue with patients.